School Library Media Specialist Collaboration with Special Education Personnel in Support of Student Learning - Farmer, Lesley S. J. (Evidence Based Library and Information Practice, 2009)
Objective – The objective of this study was to identify factors for effective collaboration between school library media specialists and special education personnel in support of student learning. Methods – A review method was used to examine illustrative studies of collaboration. Results – The analysis revealed studies that represented a variety of methodologies: survey, observation, interview, action research, and participatory ethnography. The review identified cross-study factors that facilitate collaboration between school library media specialists and special educators: shared knowledge via cross-training and regular professional interaction, effective communication skills, and effective educational team planning and co-teaching of meaningful learning activities. Conclusion – The study concluded that school library media specialists and special education personnel need to share their knowledge and expertise about the effective use of appropriate resources and services for students with special needs.